HARMFUL EFFECTS OF MOBILE PHONES ON CHILDREN (World Bulletin of Public Health, 2024)
This article tells about one of the most common and global problem- the impact of mobile phones on children’s health and harmful effects on children’s development, especially the radiations from these devices are harmful for their developing brains, the article also discusses the advantages and disadvantages of mobile phones in our life.